Hairless-knockout piglets generated using the clustered regularly interspaced short palindromic repeat/CRISPR-associated-9 exhibit abnormalities in the skin and thymus - Gao, Qing-Shan (Exp Anim, 2019)
The nuclear receptor corepressor Hairless (HR) interacts with nuclear receptors and controls expression of specific target genes involved in hair morphogenesis and hair follicle cycling. Patients with HR gene mutations exhibit atrichia, and in rare cases, immunodeficiency. Pigs with HR gene mutations may provide a useful model for developing therapeutic strategies because pigs are highly similar to humans in terms of anatomy, genetics, and physiology. The present study aimed to knockout the HR gene in pigs using the clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated-9 (Cas9) system and to investigate the molecular and structural alterations in the skin and thymus. We introduced a biallelic mutation into the HR gene in porcine fetal fibroblasts and generated nine piglets via somatic cell nuclear transfer. These piglets exhibited a lack of hair on the eyelids, abnormalities in the thymus and peripheral blood, and altered expression of several signaling factors regulated by HR. Our results indicate that introduction of the biallelic mutation successfully knocked out the HR gene, resulting in several molecular and structural changes in the skin and thymus. These pigs will provide a useful model for studying human hair disorders associated with HR gene mutations and the underlying molecular mechanisms.